2018
DOI: 10.31067/0.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Obezojenik Çevre ve Çocukluk Çağı Obezitesine Etkileri

Abstract: Global sağlık problemi olan çocukluk çağı obezitesi, kısa ve uzun dönemde sağlık, sosyal ve sosyoekonomik açıdan büyük risk taşımaktadır. Dünya çapında büyüyen çocukluk çağı obezitesini çözmek için sürekli önleyici tedbirler aranmaktadır. Obezite ile mücadelede, obez çocuk sayısı azaltılamadığı gibi mevcut artış da hızla devam etmektedir. Obezojenik çevre; obezite epidemiyolojisinden sorumlu olup aşırı yemek yeme ve hareketsizliğin desteklediği bir durumdur. Obezojenik ortamlar, toplumun veya bireyin yaşam koş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
1
1
0
9
Order By: Relevance
“…The higher NPCS sub-dimension scores in obese patients may be due to the increased search for new information about nutrition, re-evaluation of unhealthy eating behaviors and their desire to increase the tendency to healthy behaviors instead. The available data in the literature show that obese people are more exposed to environments that will create obesity risk factors compared to normalweight individuals (19,20). Our results, which supports the literature, NPCS scores, which also measure the effect of the social environment on the nutritional behavior process, are higher in obese patients.…”
Section: Discussionsupporting
confidence: 89%
“…The higher NPCS sub-dimension scores in obese patients may be due to the increased search for new information about nutrition, re-evaluation of unhealthy eating behaviors and their desire to increase the tendency to healthy behaviors instead. The available data in the literature show that obese people are more exposed to environments that will create obesity risk factors compared to normalweight individuals (19,20). Our results, which supports the literature, NPCS scores, which also measure the effect of the social environment on the nutritional behavior process, are higher in obese patients.…”
Section: Discussionsupporting
confidence: 89%
“…Any aspect of body image an individual has of his or her body is pivotally determined by interactions within obesogenic environments [57], (social) media [58], fitness imagery [59], and sociocultural experiences [59][60][61]. For example, in a study examining the impact of different forms of inspirational fitness ("fitspiration") images on women's image of their bodies, the authors found that exposure to "fitspiration" images led to decreased body satisfaction and increased negative mood over time [59].…”
Section: Body Imagementioning
confidence: 99%
“…Obezojenik çevre kavramı ilk kez 1999 yılında ortaya atılmış ve "ev ve işyerinde kilo almaya katkıda bulunan ve kilo kaybı için elverişli olmayan ortam" şeklinde ifade edilmiştir (8). Obezojenik çevrenin etkilediği en önemli mikro çevre yapısı, ev ortamı ve ebeveynlerdir (9). Yapılan çalışmalar çocuklardaki obezitenin ev ortamıyla ilişkili olduğunu göstermiştir (10,11).…”
Section: Introductionunclassified